Case Report: ITP Treatment After CAR-T Cell Therapy in Patients With Multiple Myeloma - Du, Mengyi; Huang, Linlin; Kou, Haiming; Li, Chenggong; Hu, Yu; Mei, Heng (Frontiers in Immunology, 2022)
Chimeric antigen receptor T (CAR-T) cell therapy is an attractive strategy for patients with relapsed or refractory hematological malignancies including multiple myeloma (MM). T cells are engineered to attack malignant cells that express tumor-associated antigens and better efficacy could be achieved. However, cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and hematologic toxicity are still challenges for CAR-T cell therapy. Among them, hematologic toxicity including thrombocytopenia has a longer duration and lasting effect during and after the treatment for some patients. Here we present 3 cases of hematologic toxicity manifested as refractory thrombocytopenia with platelet autoantibodies positive and plasma thrombopoietin (TPO) concentration elevated after bispecific CAR-T cell therapy in relapsed/refractory(R/R) MM patients which were successfully treated with standard therapy of immune thrombocytopenia (ITP). Without clear pathogenesis or guidance on therapy published, our cases provide a reference for the treatment of thrombocytopenia after CAR-T cell therapy and inspire exploration of the underlying pathophysiological mechanisms.